2010
DOI: 10.1007/s10544-010-9470-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-folding micropatterned polymeric containers

Abstract: We demonstrate self-folding of precisely patterned, optically transparent, all-polymeric containers and describe their utility in mammalian cell and microorganism encapsulation and culture. The polyhedral containers, with SU-8 faces and biodegradable polycaprolactone (PCL) hinges, spontaneously assembled on heating. Self-folding was driven by a minimization of surface area of the liquefying PCL hinges within lithographically patterned two-dimensional (2D) templates. The strategy allowed for the fabrication of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
159
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 33 publications
(28 reference statements)
2
159
0
Order By: Relevance
“…Although optical tweezers are able to manipulate small objects with different sizes ranging from tens of nanometers to micrometers, a substantial mechanical gripper is still desired in the absence of an energy beam and free of possible harm to living samples or influences to chemical reactions. Examples include miniaturized self-folding grippers that are actuated by differential residual stress (33), magnetic force (34), temperature (35,36), and chemicals (37,38). We show here our LPCS artificial fibrillar structures are capable of capturing microparticles with excellent selectivity.…”
Section: Selective Trapping and Releasing Of Microobjectsmentioning
confidence: 93%
“…Although optical tweezers are able to manipulate small objects with different sizes ranging from tens of nanometers to micrometers, a substantial mechanical gripper is still desired in the absence of an energy beam and free of possible harm to living samples or influences to chemical reactions. Examples include miniaturized self-folding grippers that are actuated by differential residual stress (33), magnetic force (34), temperature (35,36), and chemicals (37,38). We show here our LPCS artificial fibrillar structures are capable of capturing microparticles with excellent selectivity.…”
Section: Selective Trapping and Releasing Of Microobjectsmentioning
confidence: 93%
“…1) and are fabricated using wafer scale processes such as photolithography, wet etching, and electrodeposition, as described in detail elsewhere (24). Here, we utilized metallic hinges (lead-tin solder) and panels (nickel), but it is noteworthy that elsewhere we have shown that polyhedra can be self-assembled with polymeric panels and hinges (25), suggesting that this self- assembly paradigm would apply to diverse materials. Polyhedral self-assembly occurs after patterned nets are released from the silicon substrate on which they are fabricated and heated above the melting point of the hinge material, which in the present case requires that the templates are heated in a high boiling point solvent (N-methylpyrrolidone) above the melting point of solder (183°C).…”
mentioning
confidence: 99%
“…These mechanisms can be patterned templates or thin films which can be folded, curved, or rolled-up to become spirals, tubes, and cylindrical tubes [73,74]. Selffolding can occur spontaneously or in response to stimuli such as light, pH [75], temperature, magnetic field, or solvent [76,77]. In Figure 6, self-folding mechanism which is provided by hinges is shown briefly.…”
Section: Self-folding Polymersmentioning
confidence: 99%